Literature Review: Pathophysiology, Clinical Features and Management of Cor Pulmonale - Rameci, Hadil Hudati Awwari; Maya, Elyana Labib; Fauzan, Naufal Revaldy; Pambudi, Novanda Ayu Dila Putri; Anugrah, Yunan Prabu Jaya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Cor pulmonale refers to a condition affecting the right ventricle of the heart due to increased pulmonary pressure causing dilation or hypertrophy. This article was compiled using a literature review method. This disorder can manifest acutely, often triggered by a massive pulmonary embolism, severe pneumonia, or Acute Respiratory Distress Syndrome (ARDS), or chronically, usually caused by Chronic Obstructive Pulmonary Disease (COPD), pulmonary fibrosis, bronchiectasis, sleep apnea, or obesity-related hypoventilation syndrome. The primary cause is a disturbance in ventilation-perfusion balance that progresses to pulmonary hypertension. Symptoms usually appear in the advanced stages and include shortness of breath, fatigue, weakness, fainting with exertion, chest discomfort, abdominal swelling, lower extremity edema, wheezing, and coughing. Diagnostic evaluation includes chest radiography, computed tomography (CT scan), electrocardiography (ECG), and cardiac catheterization, the latter being the definitive method. Treatment strategies aim to correct hypoxemia, relieve right ventricular strain, and address the underlying cause of the condition.